TEACHING RECEPTIVE AND PRODUCTIVE SKILLS: READING AND WRITING - F. U. Pulatova (Modern American Journals, 2025)
This article discusses the teaching receptive and productive skills of language. It gives information about teaching reading and writing skills. The processes of reading, scanning and skimming, examples to the reading materials, stages of teaching reading: pre, while, post reading activities as well as types of writing, stages of teaching writing: pre, while, post writing is also described in this article.
Keywords: Receptive and productive skills, scanning and skimming, pre, while, post reading, types of writing, stages of teaching writing, persuasive, expository, narrative, descriptive writing.